The future of your job represents your future: a moderated mediation model of transformational leadership and job crafting. Issue 1 (2nd May 2020) - Naeem, Rana Muhammad; Channa, Khalil Ahmed; Hameed, Zahid; Ali Arain, Ghulam; Islam, Zia Ul
Abstract : Purpose: In this study, the authors aim to explain the mechanism between transformational leadership and job crafting. They predict that job-based psychological ownership (job-based PO) mediates the relationship between transformational leadership and job crafting. Furthermore, job-based PO is more effective when employees have a high level of affective organizational commitment. Design/methodology/approach: The authors collected time-lagged data through a paper–pencil survey from the sales department of large pharmaceutical companies in Pakistan. Findings: The findings of this study suggest that job-based PO mediates the positive relationship between transformational leadership and job crafting. Moreover, the relationship of job-based PO with job crafting is moderated by affective organizational commitment such that the relationship was stronger at the high levels of affective organizational commitment than that of the low levels of affective organizational commitment. Practical implications: On practical grounds, job crafting can be useful for individuals and organizations. On individuals' side, it helps them to balance their job demands and resource; on organizations' side, it provides a solution to the ongoing problem of disengaged employees and suggests managers identify new ways to support employees with their job redesign. Originality/value: This study suggests that job-based PO and affective organizational commitment are important factors that influence the relationship between transformational leadership and job crafting.